TLR4/NF-κB signaling-mediated neuroinflammation is associated with gut microbiota dysbiosis in a mouse model of Parkinson’s disease - Zhang, Ruqi; Tian, Minghan; Wu, Yangyang; Yang, Chen; Shi, Xiaoyu; Wang, Shengchun (Frontiers in Immunology, 2026)
IntroductionDysbiosis of the microbiota-gut-brain axis contribute to the neurodegenerative process of Parkinson’s disease (PD), and dysbiosis and inflammatory responses represent key mechanisms. This study aims to explore the structural changes in the composition of the gut microbiota and the alterations in the inflammatory response mediated by the TLR4/NF-κB pathway in a rotenone-induced PD mouse model, as well as the correlation between the two.MethodsThe motor coordination and spontaneous locomotor activity of the PD mouse model were evaluated using the Rota-Rod test, pole climbing test and open field test. The expression of α-synuclein (α-syn) and the activation status of the TLR4/NF-κB pathway were analyzed by western blot, quantitative real-time polymerase chain reaction (RT-qPCR) combined with immunohistochemistry. Enzyme-linked immunosorbent assay (ELISA) was used to quantitatively detect the levels of LPS and pro-inflammatory indicators TNF-α, IL-1β and IL-6. The diversity, composition structure and differential abundance of the gut microbiota were analyzed by 16S rRNA sequencing, and correlation analysis was conducted between some microbiota and inflammatory indicators related to the activation of the TLR4/NF-κB signaling pathway.ResultsMechanistic investigation revealed that rotenone activated the TLR4/NF-κB signaling pathway in the midbrain substantia nigra (SN) and colon tissues, accompanied by a significant increase in LPS levels and pro-inflammatory indicators. 16S rRNA sequencing analysis revealed that the alpha diversity of the gut microbiota were reduced in the model group, the beta diversity structure was altered. In terms of microbiota composition, at the phylum level, the relative abundance of Bacteroidota decreased, while Actinobacteria and Tenericutes increased. At the family level, the relative abundance of Lachnospiraceae and Bacteroidaceae decreased, while the relative abundance of Erysipelotrichaceae and Akkermansiaceae increased. Correlation analysis indicated that the relative abundance of specific bacterial families was significantly correlated with PD motor function indicators, the expression levels of α-syn mRNA in the midbrain SN, the TLR4/NF-κB pathway, and inflammatory indicators.ConclusionThis study demonstrates a key role of the TLR4/NF-κB signaling pathway in the microbiota-gut-brain axis of a rotenone-induced PD mouse model, where gut microbiota dysbiosis exhibits a significant correlation with inflammation induced by TLR4/NF-κB activation.